The theatrical repertoire of Amigos del Arte: between the “anarchist culture” and the “mass culture”. Mar del Plata, 1939-1947 - Dolabani, Milagros (2017)
Fil: Fil: Dolabani, Milagros; Universidad Nacional de Mar del Plata. Argentina